Pengaruh Green Marketing Dan Brand Image Terhadap Green Purchase Intention Melalui Perceived Value - Henik Hari Astuti; Eliza Eliza (Jurnal Pajak dan Bisnis, 2026)
This study aims to analyze the effect of integrating Financial Literacy and Risk Management on SME Sustainability, with Competitiveness as a mediating variable among SMEs in West Java Province. Grounded in the Resource-Based View (RBV) framework, a quantitative approach was employed using a survey method on 190 SME owners selected through purposive sampling. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) via SmartPLS software. The results show that Financial Literacy has a highly significant direct positive effect on SME Sustainability (ß = 0.754; p = 0.000), serving as the primary predictor of business survival (f2 = 0.842). Risk Management significantly enhances Competitiveness (ß = 0.589; p = 0.000) and directly affects SME Sustainability (ß = 0.168; p = 0.009). Critically, the direct effect of Financial Literacy on Competitiveness is non-significant (ß = 0.223; p = 0.110), and Competitiveness shows a non-significant effect on SME Sustainability (ß = -0.082; p = 0.120), thereby failing to act as a mediating variable (non-mediation). The structural model exhibits strong explanatory power with R2 values of 0.583 for Competitiveness and 0.682 for SME Sustainability, alongside robust predictive relevance (Q2) of 0.381 and 0.468, respectively. The implications emphasize that long-term SME survival fundamentally depends on internal financial governance and risk mitigation rather than market positioning alone. Local governments are advised to reorient SME assistance programs toward foundational financial literacy and operational risk training.